MAPlex - A massively parallel sequencing ancestry analysis multiplex for Asia-Pacific populations. (September 2019) - Phillips, C.; McNevin, D.; Kidd, K.K.; Lagacé, R.; Wootton, S.; de la Puente, M.; Freire-Aradas, A.; Mosquera-Miguel, A.; Eduardoff, M.; Gross, T.; Dagostino, L.; Power, D.; et al.
Highlights: Large-scale ancestry-informative marker panel assembled for Ion Torrent-based massively parallel sequencing. The first time single-site binary and multiple-allele SNPs plus microhaplotypes have been combined in a forensic test. Extensive reference and test population samples compiled for STRUCTURE genetic cluster analysis in several hundred worldwide populations. STRUCTURE data shows optimum differentiation of seven population groups; distinguishing Middle East and South Asian individuals efficiently. Abstract: Current forensic ancestry-informative panels are limited in their ability to differentiate populations in the Asia-Pacific region. MAPlex (Multiplex for the Asia-Pacific), a massively parallel sequencing (MPS) assay, was developed to improve differentiation of East Asian, South Asian and Near Oceanian populations found in the extensive cross-continental Asian region that shows complex patterns of admixture at its margins. This study reports the development of MAPlex; the selection of SNPs in combination with microhaplotype markers; assay design considerations for reducing the lengths of microhaplotypes while preserving their ancestry-informativeness; adoption of new population-informative multiple-allele SNPs; compilation of South Asian-informative SNPs suitable for forensic AIMs panels; and the compilation of extensive reference and test population genotypes from online whole-genome-sequence data for MAPlex markers. STRUCTURE genetic clustering software was used to gauge the ability of MAPlex to differentiate a broad set of populations from South and East Asia, the West Pacific regions of Near Oceania, as well as the other globally distributed population groups. Preliminary assessment of MAPlex indicates enhanced South Asian differentiation with increased divergence between West Eurasian, South Asian and East Asian populations, compared to previous forensic SNP panels of comparable scale. In addition, MAPlex shows efficient differentiation of Middle Eastern individuals from Europeans. MAPlex is the first forensic AIM assay to combine binary and multiple-allele SNPs with microhaplotypes, adding the potential to detect and analyze mixed source forensic DNA.